Are Cities Illiberal? Municipal Jurisdictions and the Scope of Liberal Neutrality - Turmel, Patrick (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
One of the main characteristics of today’s democratic societies is their pluralism. As a result, liberal political philosophers often claim that the state should remain neutral with respect to different conceptions of the good. Legal and social policies should be acceptable to everyone regardless of their culture, their religion or their comprehensive moral views. One might think that this commitment to neutrality should be especially pronounced in urban centres, with their culturally diverse populations. However, there are a large number of laws and policies adopted at the municipal level that contradict the liberal principle of neutrality. In this paper, I want to suggest that these perfectionist laws and policies are legitimate at the urban level. Specifically, I will argue that the principle of neutrality applies only indirectly to social institutions within the broader framework of the nation-state. This is clear in the case of voluntary associations, but to a certain extent this rationale applies also to cities. In a liberal regime, private associations are allowed to hold and defend perfectionist views, focused on a particular conception of the good life. One problem is to determine the limits of this perfectionism at the urban level, since cities, unlike private associations, are public institutions. My aim here is therefore to give a liberal justification to a limited form of perfectionism of municipal laws and policies.